2022
DOI: 10.3390/ijerph19031850
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Self-Medication with Cannabis in Young Adults with Hazardous Cannabis Use

Abstract: Using cannabis to reduce psychological and physical distress, referred to as self-medication, is a significant risk factor for cannabis use disorder. To better understand this high-risk behavior, a sample of 290 young adults (ages 18–25; 45.6% female) were recruited from two U.S. universities in January and February of 2020 to complete a survey about their cannabis use and self-medication. Results: seventy-six percent endorsed using cannabis to reduce problems such as anxiety, sleep, depression, pain, loneline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…This preference for CBD-dominant products was previously observed by Turna et al (35% of exclusive medical users versus 10% of mixed users reported using products with low THC/high CBD concentration (Turna et al 2020 ). In most of the previous studies of self-medication with cannabis, information regarding the doses or ratios of THC and CBD was not provided to allow further comparisons with our data (Wallis et al 2022 ; Greenwald et al 2021 ; Osborn et al 2015 ; Sinclair et al 2020 ; Hansen et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This preference for CBD-dominant products was previously observed by Turna et al (35% of exclusive medical users versus 10% of mixed users reported using products with low THC/high CBD concentration (Turna et al 2020 ). In most of the previous studies of self-medication with cannabis, information regarding the doses or ratios of THC and CBD was not provided to allow further comparisons with our data (Wallis et al 2022 ; Greenwald et al 2021 ; Osborn et al 2015 ; Sinclair et al 2020 ; Hansen et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted before the legalization of recreational cannabis in Canada showed a similar portrait (mean age was 31.1 years for recreational + medical users versus 40.7 years for exclusive medical users) (Turna et al 2020 ). In a recent study that included young US participants (aged 18–25 years) with hazardous cannabis use, older individuals were more likely to self-medicate their pain with cannabis (Wallis et al 2022 ). In our survey, the observed similar proportion of men and women is not consistent with previous surveys of cannabis users (Turna et al 2020 ; Lucas and Walsh 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests a real connection between cannabis use and physical health problems. What is more, young adults (18–25 years) may use cannabis as self-medication to reduce physical and mental distress [ 40 ], and further, it has been shown, that pain relief is the primary motivation for cannabis users with chronic pain [ 41 ]. The causal relationship has, however, not sufficiently been studied among adolescents as cannabis use may increase the risk of physical health problems, and physical health problems may be a risk factor for cannabis use.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the United States involving healthy populations have shown that Black youth are more likely than White youth to report self-medicating with cannabis to relieve physiological symptoms associated with anxiety [ 65 ]. However, many studies suggest that youth use cannabis because they believe it will alleviate anxiety symptoms regardless of race, but no studies to date indicate that youth self-medicate to ease psychosis symptoms [ 66 , 67 ]. This study is unique because it will explore the intersections of race, ethnicity, and cannabis use among young people experiencing their first episode of psychosis.…”
Section: Discussionmentioning
confidence: 99%